2013
DOI: 10.1590/s0100-72032013000600007
|View full text |Cite
|
Sign up to set email alerts
|

Evolução perinatal e pediátrica de crianças com translucência nucal aumentada e cariótipo normal

Abstract: (45,6%). Nos fetos com cariótipo normal, houve um abortamento na 15ª semana gestacional com pentalogia de Cantrel, um óbito na 24ª semana com diversas anomalias estruturais, um óbito neonatal sem causa definida e dois casos de comunicação intraventricular (CIV) detectados no ECO fetal. Na avaliação ecocardiográfica pós-natal, persistiu um caso de CIV e foi diagnosticado um caso de comunicação interatrial (CIA) e persistência do canal arterial (PCA). Entre os 40 casos sobreviventes, apenas 1 criança apresentou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(56 reference statements)
0
1
0
1
Order By: Relevance
“…Por otra parte, Vieira et al 20 , en un gran estudio de seguimiento, analizaron los resultados de los fetos con aumento de TN y reportan que el 54.4% de dichos fetos eran euploides y que el 93.5% de estos fetos tuvieron partos y desarrollo postnatal normales, concluyendo que el aumento de TN con cariotipo normal y un estudio ecográfico morfológico-ecocardiográfico del segundo trimestre sin alteraciones, la probabilidad de que el niño nazca vivo y sano es alta.…”
Section: Discussionunclassified
“…Por otra parte, Vieira et al 20 , en un gran estudio de seguimiento, analizaron los resultados de los fetos con aumento de TN y reportan que el 54.4% de dichos fetos eran euploides y que el 93.5% de estos fetos tuvieron partos y desarrollo postnatal normales, concluyendo que el aumento de TN con cariotipo normal y un estudio ecográfico morfológico-ecocardiográfico del segundo trimestre sin alteraciones, la probabilidad de que el niño nazca vivo y sano es alta.…”
Section: Discussionunclassified
“…In a large follow-up study, Vieira et al [11] analyzed the outcomes of fetuses with increased NT and found that 54.4% of such fetuses were euploid and that 93% of these fetuses had normal births and immediate postnatal development, with only 3 cases involving miscarriage or neonatal death. In our study, outcomes were normal status at birth for 54% of fetuses, including 40 out of the 58 euploid cases (69%), and perinatal complications in 17% of cases.…”
Section: Discussionmentioning
confidence: 99%